Pemanfaatan Lahan Terbatas Dengan Menggunakan Teknik Vertikultur Di KWT Dewi Sartika Kelurahan Sentul - Arifatur Rahma Putri; Muhamad Arlyen Sahdan; Sita Nadifatul Ilmi; Adistia Nurul Aini; Ida Syamsu Roidah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Increasing population density is now affecting all aspects. Spatial planning that is not conducive affects the level of community welfare. Reduced land makes people unable to grow crops to the fullest. Modern agriculture can be implemented in a simple way, namely starting from the family environment by utilizing narrow land or through the use of land that is not large. Utilization of land that is not large is by using a verticultural cropping system which can overcome the narrowness of the land. The activities carried out were at KWT Dewi Sartika, to be precise, in the Sentul Village, Blitar City. The activities carried out are counseling and mentoring regarding the incorporation and application of verticultural methods in dealing with less extensive land. The implementation of this activity aims to educate the public regarding the use of narrow land for conventional, organic and commercial farming. This activities also aims to update the vertical system that has been carried out by the community.